DUAL APPROACH ON THE WEST, THE INFLUENCE OF LAS MENINAS ON HERMAN BRAUN-VEGA'S PIECE - Santa Cruz Bustamante, Cesar Octavio (2010)
After visiting the Picasso Museum in Barcelona in 1968, Herman Braun-Vega was deeplyimpressed by a series of Picasso's paintings based on Velázquez's Las Meninas. Thisseries of paintings will intluence bis style thereafter, leaving its mar k in severa! of bisworks such as Duat Approach on the West ( 1987), which contains references from LasMeninas and from Guernica, as well as allusions to Latin American society and contemporaryhistory.